AVIAN REOVIRUSES - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT: The members of the orthoreovirus genus are distinguishable into two distinct groups: those of avian origin, and thrive of mammalian origin (Kawamura and Tsubahara, 1966). Both groups of viruses have a genome consisting of 10 segments of double-stranded RNA (dsRNA), separable into three size classes, which are enclosed within a double protein capsid shell 70 to 80 nm in diameter with a similar protein composition and distribution (Spandidos and Graham, 1976